Perancangan WebGIS sebagai Daya Tarik Destinasi Wisata Bahari di Raja Ampat - Fitriyani, Sakila Divia; Vinsa Qatrunnada; Dini Dwi Andini; M. Fahri; Lestari, Della Ayu; Silaban, Joy Elisabeth; Ramadhani, Tirta Samudera (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Indonesia, with 17,540 islands spread from Sabang to Merauke, is known as a maritime country with extensive natural potential, especially in marine tourism. One of the famous marine tourism potentials is Raja Ampat or known as "last paradise on earth." The marine tourism management process still needs to be improved. This research aims to design WebGIS, using GIS technology and other software, to help increase information about marine tourism destinations in Raja Ampat. The research method applied uses the waterfall model, which includes analysis, design, and system implementation. This research resulted in designing a WebGIS system that makes it easier for users to find information about marine tourism destinations in Raja Ampat. WebGIS is an innovative solution to overcome this challenge, so that tourists can find out about tourist infrastructure in Raja Ampat easily and quickly. It is hoped that this will improve the tourist experience and support the management of marine tourismto be more effective, especially in Raja Ampat.